2008
DOI: 10.1111/j.1095-8312.2007.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Bite force in vertebrates: opportunities and caveats for use of a nonpareil whole-animal performance measure

Abstract: Measurements of whole-organism performance traits have been useful in studies of adaptation and phenotypeenvironment correlations. Bite force capacities may be tightly linked to both the type and magnitude of the ecological challenges of food acquisition, mate acquisition, and antipredation in vertebrates. In the present study, we present technical details on bite meters and on measuring bite forces. The ability to take reliable measurements depends on specific features of the measuring device and on where in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
188
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(192 citation statements)
references
References 82 publications
4
188
0
Order By: Relevance
“…First, is size evolution associated with ecological divergence of carnivorous species from insectivorous ancestors? For a given skull morphology, bite force and gape scale positively with body size in vertebrates [29][30][31][32], and this performance trait can explain food resource use, including the consumption of mechanically challenging foods [32,33]. Thus, we hypothesize that carnivorous bats experienced selection on body size.…”
Section: Introductionmentioning
confidence: 95%
“…First, is size evolution associated with ecological divergence of carnivorous species from insectivorous ancestors? For a given skull morphology, bite force and gape scale positively with body size in vertebrates [29][30][31][32], and this performance trait can explain food resource use, including the consumption of mechanically challenging foods [32,33]. Thus, we hypothesize that carnivorous bats experienced selection on body size.…”
Section: Introductionmentioning
confidence: 95%
“…All available data from a broad range of durophagous taxa show that bite forces increase disproportionately relative to changes in head and body dimensions across ontogeny (i.e. positive allometry) (Herrel and Gibb, 2006;Anderson et al, 2008). These results suggest that the scaling of traits related to musculoskeletal biomechanics is most likely to explain the allometric patterns of bite force among durophagous taxa Herrel and O'Reilly, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have also shown that individuals with higher bite forces require less time to consume certain prey items (Herrel et al, 2001;Verwaijen et al, 2002;Van der Meij and Bout, 2006). This suggests that an additional benefit of developing allometrically greater bite forces is that durophagous taxa can increase the net rate of energy intake when foraging (optimal foraging) (MacArthur and Pianka, 1966), and presumably enhance their fitness (Anderson et al, 2008). Because the implications for growth patterns that facilitate high bite-force generation are apparent (Kolmann and Huber, 2009), the feeding systems of durophagous taxa are well suited for investigations of the scaling relationships between musculoskeletal growth, feeding performance and dietary ontogeny.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These studies typically assume accurate measurements of performance, which can be difficult to obtain, sometimes with a few observations contributing to a final point estimate of performance, especially when maximum performance values are of interest (Anderson et al, 2008;Garland and Losos, 1994). For the initial approval of projects by animal use and collection review boards, it is also necessary to plan for the number of individuals to be tested, the testing procedure for each individual and the resulting statistical power of the results.…”
Section: Introductionmentioning
confidence: 99%